Shaft-sensorless control of permanent magnet synchronous motors using a sliding observer - Chin, KP; Hong, ZH; Wang, HR (My University, 1996)
In this paper, two nonlinear sliding observers are developed for speed-sensorless control of permanent magnet synchronous motors. One of the observer estimates the rotor position and velocity based on the current measurement. The other observer estimates the load torque in addition to the rotor position and velocity. Both theoretical analyses and experiments show that, using either observer for speed-sensorless control, the steady-state velocity error converges even when there is an external load torque applied to the rotor. However, when the external load is present, the position estimation error of the control system with torque estimation and compensation is much small than the system without torque estimation and compensation.